Level Keputusan Moral Remaja Berdasarkan Etnis - Yenni Rizal (Jurnal Psikologi Pendidikan dan Konseling: Jurnal Kajian Psikologi Pendidikan dan Bimbingan Konseling, 2017)
This study is designed to describe the rate of multiethnic adolescent moral judgement development in West Borneo. The data analysis used is seeking for score P by summing up scores of stages 5A, 5B, and 6 for either each criteria or totality. This score P may be interpreted as score of subject moral judgment in making a decision, then index score is looked for. Furthermore, the index score is conversed into score T. Highest score T obtained by respondent represent the inclination of moral development level. Adolescent moral decision based on the research findings suggest highest Post Conventional level is native ethnic groups of Madura, whereas lowest Post Conventional level is Chinese ethnics. Conclusion in this study is each ethnic having high collectivism culture is not definite yet at high Post Conventional level.